IMPLEMENTASI METODE GARIS LURUS DAN GARIS LENGKUNG PADA APLIKASI PERAMALAN PENJUALAN EMAS PADA TOKO EMAS AGUNG - Ady Wijaya; Sudirman; Arfan Yunus (STMIK KHARISMA Makassar, 2018)
Gold sales are activities or businesses selling gold products. Because of the capital spent is very much, there is a need for forecasting to plan ahead. This study designed a weekly sales forecasting system and sales of gold orders per month using the linear model (least square trend) and quadratic model (quadratic trend). To determine the appropriate method, Forecast Error Standard was used. In this application making prosess, the author used Visual Basic 2013 programming language and MySQL as database. Testing method used by the author is the Black Box. The result can be stated that system that was created by the author goes according to plan and the specification needs. Based on the result of research and testing, it can be concluded that the author has managed to build gold sales forecasting system using the linear model (least square trend) and quadratic model (quadratic trend) at Agung Gold stores